Smallholder dairying: Better marketing or better feeding—Which comes first? - Teufel, Nils; Mundy, Paul; Duncan, Alan J. (International Livestock Research Institute, 2016)
This animation describes how the ILRI-supported MilkiT project set up innovation platforms to understand the needs of smallholder farmers' in India and Tanzania to help them better feed their animals and sell more milk.